Pinning out pathological specimens – are we risking an unnecessary escalation of treatment?. Issue 5 (May 2015) - Varley, I.; Mathew, B.; Karsai, L.; Crank, S.T.
Abstract The importance of surgical resection margins is paramount, and it is vital that they are accurately delineated so that clinicians' decisions about adjuvant treatment can be validated. Pathological specimens therefore are often pinned to aid orientation and maintain mucosal margins. However, in cadaveric resections of bovine tongues, pinning of the specimens significantly reduced the depth of tissue. In clinical practice, if results are affected by the fixation method and not based on the true margins, it could profoundly influence the use of adjuvant treatment in patients with cancer. Pinning the specimens with the mucosal surface against the board will maintain any theoretical benefit for the mucosa and does not compress the specimens.